Analisis Perubahan Hukum Ketenagakerjaan pada UU Cipta Kerja Mengenai Perlindungan Hak Pekerja - Nikmah Dalimunthe; Fitria Nurhaliza (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this research is to find out how workers are protected with the various modifications to the definition of employment relationship after the enactment of the Job Creation Law. The employment relationship serves as the basic standard for the protection of the parties, as is well known. Employment relationship is a legal arrangement relating to employment between two legal subjects. Basically, the employment relationship is between an employer and a worker, and is governed by laws that determine rights, obligations, and working conditions. This makes it clear what the rights and obligations of each party are. The type of employment relationship was changed with the passing of the Job Creation Law, which also expanded the model of employment relationship and shifted the idea of labor supply agreements to outsourcing. With these changes, it becomes unclear how the industrial relations principles in the Job Creation Law and the protection of the parties in the employment relationship can be established. This research combines descriptive and normative legal research methods. The definition of a worker service provision agreement is changed to outsourcing, the model of employment relationship is expanded, and new types of employment relationships are brought about by the implementation of the Job Creation Law. These changes raise the question of how protection. The research findings show that the Job Creation Law contains three different types of employment relationships: permanent, temporary, and flexible. The latter is based on job completion or part-time work, and the agreement on the provision of worker services only changes the term to outsourcing. However, the concept of employment relationship remains the same as before, and this deviates from what is considered an ideal concept of employment relationship as it involves three parties: the employer, the service provider, and the worker. Therefore, the definition of employment relationship contained in the Job Creation Law is based on the mechanism of agreement between the parties, such as the duration of PKWT and the right to extended rest periods that can be specified in the employment agreement. As a result, it can be said that the state has less control over the employment relationship, which makes it more difficult to establish industrial relations as the legal relationship of the parties is more focused on the private sector and there is less government intervention. As a result, workers find it difficult to obtain protection and legal certainty amidst fierce competition for jobs. Keyword: Employment Relations, Job Creation Law, Workers